Words as Events: Cretan Mandinádes in Performance and Composition - Sykäri, Venla (Studia Fennica Folkloristica, 2011)
"Words as Events introduces the tradition of short, communicative rhyming couplets, the mantinádes, as still sung and recited in a variety of performance situations on the island of Crete. Recently, these poems have also entered modern mass media and they are widely being exchanged as text messages by Cretans. Focusing on the multi-functionality of the short form, Sykäri demonstrates how the traditional register gives voice to individual experiences in spontaneous utterances. The local focus on communicative economy and artistry is further examined in a close analysis of the processes and ideals of composition. By analyzing how the "restrictions" of form and performative conventions in fact generate impulses of creativity, the author creates a theoretical approach that is sensitive to the special characteristics of the short, rhymed poetic traditions. In this interdisciplinary study, the reader is invited to become familiar with the current folklore theory of oral poetry, which has a long tradition in Finland. The author combines the results of earlier folkloristic and anthropological insights, and extends the theoretical concerns further to address questions of spontaneity and individual agency. The research data has been produced in communicative interactions during long-term fieldwork. As a result, the short, rhymed poetry, often neglected by scholars in earlier research paradigms, can now be seen in new light - specifically as dialogic poetry - through its extended, multi-layered dialogic qualities."